Long-term seismicity of the Reykjanes Ridge (North Atlantic) recorded by a regional hydrophone array - Goslin, J. (2018)
The seismicity of the northern Mid-Atlantic Ridge was recorded by two hydrophone networks moored in the sound fixing and ranging (SOFAR) channel, on the flanks of the Mid-Atlantic Ridge, north and south of the Azores. During its period of operation (05/2002-09/2003), the northern 'SIRENA' network, deployed between latitudes 40 degrees 20'N and 50 degrees 30'N, recorded acoustic signals generated by 809 earthquakes on the hotspot-influenced Reykjanes Ridge. This activity was distributed between five spatio-temporal event clusters, each initiated by a moderate-to-large magnitude (4.0-5.6 M) earthquake. The rate of earthquake occurrence within the initial portion of the largest sequence (which began on 2002 October 6) is described adequately by a modified Omori law aftershock model. Although this is consistent with triggering by tectonic processes, none of the Reykjanes Ridge sequences are dominated by a single large-magnitude earthquake, and they appear to be of relatively short duration (0.35-4.5 d) when compared to previously described mid-ocean ridge aftershock sequences. The occurrence of several near-equal magnitude events distributed throughout each sequence is inconsistent with the simple relaxation of main shock-induced stresses and may reflect the involvement of magmatic or fluid processes along this deep (>2000 m) section of the Reykjanes Ridge.